2004
DOI: 10.1074/jbc.m309284200
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Translocation of Rac2 and the NADPH Oxidase Component p67 during Phagocytosis

Abstract: In this study, the translocation of the NADPH oxidase components p67 phox and Rac2 was studied during phagocytosis in living cells. For this purpose, green fluorescent protein (GFP)-tagged versions of these proteins were expressed in the myeloid cell line PLB-985. First, the correct localization of p67GFP and GFP-Rac2 was shown during phagocytosis of serum-treated zymosan by wild-type PLB-985 cells and PLB-985 X-CGD (chronic granulomatous disease) cells, which lack expression of flavocytochrome b 558 . Subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 35 publications
9
51
0
Order By: Relevance
“…We reported that p47 phox accumulates transiently on phagocytic cups and mature phagosomes during Fc␥R-mediated phagocytosis (Ueyama et al, 2004), consistent with earlier studies showing p47 phox and p67 phox associate with both nascent and mature phagosomes in neutrophils and neutrophil-like PLB-985 cells (Allen et al, 1999;van Bruggen et al, 2004). The present study shows that GFP-p40 phox also transiently associates on phagosomes, although this targeting is initiated at later stages after phagosome sealing.…”
Section: Discussionsupporting
confidence: 79%
“…We reported that p47 phox accumulates transiently on phagocytic cups and mature phagosomes during Fc␥R-mediated phagocytosis (Ueyama et al, 2004), consistent with earlier studies showing p47 phox and p67 phox associate with both nascent and mature phagosomes in neutrophils and neutrophil-like PLB-985 cells (Allen et al, 1999;van Bruggen et al, 2004). The present study shows that GFP-p40 phox also transiently associates on phagosomes, although this targeting is initiated at later stages after phagosome sealing.…”
Section: Discussionsupporting
confidence: 79%
“…It has been reported that p47 phox and Rac2 can be translocated without any translocation of p67 phox in lipopolysaccharide-stimulated neutrophils, which gives some credence to this hypothesis (15). Recently, Van Bruggen et al (51) found that the translocation of p67 phox and Rac2 is a cyclic process depending on the integrity of the actin network, in which flavocytochrome b 558 -bound p67 phox and Rac2 are continuously exchanged for free p67 phox and Rac2. The contribution of lipid rafts to the efficient activation of NADPH oxidase has been investigated in neutrophils, and suggests that the assembly of the enzyme complex depends on multiple, cooperative binding and signaling interactions that are greatly facilitated in a raft environment (24,52).…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that p40 phox also undergoes conformational changes by disruption of the intramolecular PX-PB1 domain interaction to enable the ternary cytoplasmic complex to bind to PI(3)P-enriched membranes (11). Finally, Rac translocates to phagosomes (12,13) in a GTP-dependent manner (14,15), resulting in generation of superoxide anion by the transfer of electrons from cytoplasmic NADPH to molecular oxygen.…”
Section: N Phagocytic Cells Reactive Oxygen Species (Ros)mentioning
confidence: 99%